Perceptions and Practices of the Ideal Teacher Instructional Delivery - Culajara, Carla Jobelle; Buenaventura Luces (MASI Mandiri Edukasi, 2023)
Teachers play a crucial role in improving every lesson's calibre at this stage of the teaching and learning process. The teacher has to keep up with all the complications that develop due to the quick changes in the teaching and learning process. This study aims to learn what excellent teachers mean to school administrators. The study's goals were to: (1) identify the personal, professional, and instructional competence of an ideal teacher; (2) explore how these traits impact how instruction is delivered; and (3) create a framework that takes these traits into account. The study used a participatory action research methodology with a qualitative research design. Four department heads and three master teachers took part. The study used a qualitative research design employing participatory action research. It was participated by 4 Department Heads and 3 Master Teachers in Classroom Observation and focus group discussion (FGD). Purposive sampling was used in choosing participants. Based on the findings, themes emerged: compassion, flexibility, adaptability, adapting (Vision, Mission, Goals, and Objectives) VMGO, setting standards using (Philippine Professional Standards for Teachers) PPST and creating solid linkages and involvement, and student-centred learning. The novel the research addresses the importance of Classroom Observation and how to become an ideal teacher in the 21st century.